2019
DOI: 10.3390/nu11123048
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Alcohol Intake in Non-Alcoholic Fatty Liver Disease: To Drink or Not to Drink?

Abstract: Nonalcoholic fatty liver disease (NAFLD) is defined by hepatic steatosis in the presence of alcohol intake within safe limits, defined by guidelines of scientific associations (usually 20 g or 2 units/day in women, 30 g or 3 units in men). The diagnosis is usually followed by medical counseling of total abstinence, in order to prevent disease progression. This policy has been challenged by epidemiological studies, suggesting that the risk of liver disease and disease progression is lower in modest drinkers tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 97 publications
0
26
0
Order By: Relevance
“…Although the effect of active smoking on NAFLD development remained controversial [ 222 ] a recent systematic review and meta-analysis from 20 observational studies revealed a slight but significant association between active and passive smoking and NAFLD [ 223 ]. The link between a modest alcohol consumption with NAFLD development is described in a very recent review [ 224 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the effect of active smoking on NAFLD development remained controversial [ 222 ] a recent systematic review and meta-analysis from 20 observational studies revealed a slight but significant association between active and passive smoking and NAFLD [ 223 ]. The link between a modest alcohol consumption with NAFLD development is described in a very recent review [ 224 ].…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol intake is an exclusion criterion for NAFLD clinical trials (>20 g and >30 g per day in men and women, respectively), although its baseline assessment is suboptimal, and the benefits or harms of its intake are controversial. 19 Irrespective of baseline parameters, patients receiving placebo show significant histologic, radiologic, and biochemical responses. 8 This means that patients change their behaviour after enrolment (Hawthorne effect), indirectly reflecting the impact of lifestyle on response rates (not only on the placebo but also on the experimental group).…”
Section: Impact Of Comorbidities and Lifestyle On Treatment Responsementioning
confidence: 99%
“…Changes in body weight and physical activity should be recorded and included in the final analysis to avoid potential biases. Quantification of alcohol intake is also challenging, with consistent variability in drinking patterns within NAFLD thresholds, which is likely to influence the results 183. Finally, gene polymorphisms associated with NASH ( PNPLA3 I148M and TM6SF2 E167K ) are likely to affect trial response.…”
Section: Placebo and Risk Stratification In Clinical Trialsmentioning
confidence: 99%